Absorbing–generating seaward boundary conditions for fully-coupled hydro-morphodynamical solvers - Incelli, Giorgio; Briganti, Riccardo; Dodd, Nicholas (Elsevier, 2015)
This paper presents a new technique to compute open boundary conditions for fully-coupled hydro-morphodynamical numerical solvers based on the Non-Linear Shallow Water and the Exner equations. These conditions allow the generation of incident signals and the absorption of reflected ones, taking into account the bed evolution at the boundary. They use the approximations for linear waves in shallow water and are based on the solution of the Riemann Equations.